SOME FEEDBACK ABOUT LYRICAL GENRE (Scientific journal of the Fergana State University, 2023)
The article discusses the problem of dividing lyrical poems into genres. At the same time, I. Sulton, B.Sarimsoqov, H.Umurov, D.Quronov, based on the principles of classification, paid special attention to the diversity in the formation of lyrical genres and the role of topography in the formation of the genre.